Prevalence and risk factors of chronic kidney disease among commercial motorcyclists in Ado-Ekiti, Ekiti State, Nigeria - Funmilayo A. Ibitoba; Oluwaseyi A. Akpor; Oghenerobor B. Akpor (Scientific African, 2022)
Chronic kidney disease (CKD) is a silent killer that has become a global public health issue in the past decades and affects more than 10% of the population worldwide. The study aimed to investigate the prevalence and risk factors of CKD among commercial motorcyclists in Ado-Ekiti. The study adopted a descriptive cross-sectional survey design. A multistage sampling technique was employed to select 310 respondents. Socio-demographic data, knowledge, and risk factors for CKD were determined using a standardized questionnaire while CKD prevalence and incidence of end stage renal disease were investigated with biophysical measurements and laboratory investigations. Descriptive analyses were used to answer the research questions while inferential statistics were used to test hypotheses at a significant level of p < 0.05. Socio-demographic characteristics of the respondents revealed that the majority (69.5%) were between 21 and 40 years. About one-third (35.5%) have poor knowledge of CKD. A CKD prevalence of 22.3% was recorded with more than half (58.8%) in the second stage with no record of end-stage renal disease. Major risk factors of CKD identified were herbal concoction (96.4%), alcohol (72.8%), NSAID (64.9%), hypertension (33.4%), and diabetes mellitus (10.2%). There was a significant relationship between respondents’ knowledge of CKD and educational background (χ2 = 89.934, p = < 0.001) and age (χ2 = 22.899, p = 0.001). Diabetes and hypertension were the only two risk factors that significantly predicted CKD. The study concluded that the prevalence of CKD among the studied population is high and that diabetes and hypertension were the major predictors CKD among commercial motorcyclists.